Analysis on Risk, Real Returns, and Performance Measurement of Sharia Stocks and Non-sharia Stocks - Yoyok Prasetyo; Ahmad Azam Sulaiman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Indonesia is predominantly Muslim, however, this does not necessarily mean that the number of sharia stock investors in Indonesia is also large. Referring to SOTS data’s, the number of sharia stocks investors is still very small compared to the number of stock investors as a whole. Therefore, research is needed to understand the comparison of risks, returns, and performance measurement of sharia and non-sharia stocks. Using purposive sampling, a sample of 19 stocks were obtained consisting of 14 sharia stocks and 5 non-sharia stocks from 2014 to 2018. This research is an explanatory comparative method and is a quantitative type using a different test. The results show that there is a difference in risk between sharia and non-sharia stocks. However, there is no difference in yields between Sharia and non-Sharia stocks. Performance measurement based on Risk-Adjusted Performance using the Sharpe ratio show that non-Sharia stocks are more dominant in performance than Sharia stocks. Total risk (SD) of sharia stocks (7.945062) is higher and is somewhat bigger than the average non-sharia stock risk (6,186363) and the real returns between sharia and non-sharia stocks, although descriptively statistical the real returns of sharia stocks (0.066179%) is lower than the non-sharia stocks (1.175495%).